Asset Volatility and Financial Sustainability - Jiahua Zhou (European Scientific Journal, ESJ, 2023)
This study observes how companies’ fundamental-based asset volatility impacts their financial sustainability. Accounting literature documents that net assets value accumulates previous earnings management. The asset balance change reflects biased earnings measurement, and abnormal asset fluctuation signals aggressive earnings management. This paper uses delisting as a proxy to observe how asset volatility can interact with abnormal earnings fluctuation to impact firms’ sustainability. The study uses two groups of regression and a Principal Component Analysis (PCA) Logistic Regression approach to observe how asset volatility impacts companies’ delisting risk. It borrows the Six Sigma methodologies to measure the volatility of financial statement items. Then the PCA analysis reduces the data dimensions to twelve factors. The analysis shows that assets’ abnormal fluctuation is a risk signal concurring with the extant earnings management literature. One takeaway from this study is that companies must disclose detailed explanations if asset volatility is beyond a red line. As Statement of Financial Accounting Standards (SFAS) 151 requires direct disclosure of abnormal excess capacity costs, companies must disclose abnormal asset volatility. The paper contributes to the literature from two perspectives. First, this paper captures firms’ sustainability from the accounting perspective with fundamental measures from quarterly financial reports. It provides a comprehensive way to detect aggressive earnings management risks. Second, the PCA logistic regression model offers a comprehensive analysis to derive useful information from many attributes.